Pengaruh Jumlah Uang Beredar (M1) dan Suku Bunga BI (BI Rate) Terhadap Tingkat Inflasi di Indonesia - Marta Elvina; A. A. Sri Purnami; I Gusti Ayu Athina Wulandari (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2021)
The purpose of this research is to analyze the effect of the Money Supply (M1) and the BI Interest Rate (BI Rate) on the existing inflation rate in Indonesia, both simultaneously and partially. The data analysis method in this case uses Multiple Linear Regression Analysis, Classical Assumption Test, F test and t test. The results of the research simultaneously show that the Money Supply (M1) and the BI Interest Rate (BI Rate) can have a significant influence on inflation in Indonesia. The results of the study partially show that the Money Supply (M1) can have a negative and significant effect on inflation. Meanwhile, partially the BI Interest Rate (BI Rate) can have a positive and significant effect on inflation in Indonesia.